Phylogenetic analysis of rabies virus in the state of Rio Grande do Sul, Southern Brazil (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies is a worldwide zoonosis caused by rabies virus (RABV), a member of the Lyssavirus genus, family Rhabdoviridae. In nature, RABV is maintained in cycles with distinct natural reservoirs. In the urban cycle, the main reservoir for the virus is the domestic dog, on the other hand, in the sylvatic cycle different species can be the reservoir. In Latin America, the main natural RABV reservoir is the haematophagous bat Desmodus rotundus. However, RABV lineages adapted to different bat species, including insectivorous and frugivorous bats, have been frequently reported. The RABV lineages isolated from non haematophagous bats are genetically distinct from the RABV lineages whose natural reservoirs are haematophagous bats. In the State of Rio Grande do Sul (RS), southern Brazil, urban rabies has not been detected since 1988. Nevertheless, rabies remains endemic in haematophagous and non haematophagous bat species. The present work reports the first phylogenetic analyses on RABV isolates from the State of RS, for that, a total of 30 rabies virus (RABV) isolates sent to rabies diagnosis were analyzed. The isolates were recovered from different bat species (Tadarida brasiliensis, Myotis nigricans and Histiotus velatus), from herbivores (bovines and buffalo) and carnivores (domestic dog and cat). The bat species were identified with the aid of a morphological dichotomous key. For the phylogenetic analysis, total RNA was extracted from original brains (herbivores and carnivores) or infected mice (bats) with Trizol and submitted to reverse transcription/polymerase chain reaction (RT-PCR) with primers targeting a initial portion of the nucleoprotein gene (N). Phylogenetic analysis of the sequenced fragments revealed the occurrence of four RABV lineages, named after its natural hosts: Desmodus rotundus (haematophagous bat), Tadarida brasiliensis (insectivorous bat), Myotis nigricans (insectivorous bat) and Histiotus velatus (insectivorous bat). All RABV isolates from herbivores belonged to the haematophagous bat Desmodus rotundus lineage. The two RABV isolates from carnivores clustered within the Tadarida brasiliensis lineage, revealing two occasional spillovers from insectivorous bats to domestic pets, thus not compromising the status of “urban rabies free” of the area. These findings highlight the importance of the identification of RABV lineages and its value as an aid to support rabies surveillance.